PROPAGATION OF Cnidoscolus aconitifolius USING STEM CUTTINGS AT DIFFERENT MATURITY STAGES AND GROWING MEDIA - Fitra Gustiar Mashadi; Benyamin Lakitan; Dedik Budianta; Zaidan P Negara; M. Umar Harun; Susilawati Susilawati; Straiker Ali Muda (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Chaya leaves (Cnidoscolus aconitifolius (Mill.) I.M. Johnst.) are leafy vegetables that contain many vitamins and minerals. Information about the intensification of chaya cultivation is still rare. Chaya propagated by stem cuttings. The maturity level of stem cuttings and planting media were expected to affect the success of plant propagation. This study aims to determine the maturity level of cuttings material that can grow well and deter-mine the type of media that can support the growth of chaya propagation. This research has been carried out from July to October 2022 in an off-campus experimental outdoor facility located in Inderalaya, South Suma-tra. This study was conducted using a randomized block design with 2 factors. The first factor was the level of maturity of stem cuttings material (upper, middle, and basal), and the second factor was the type of growing medium (control, chicken manure, and cow manure). The results showed that the use of cuttings from the mid-dle and basal has a better percentage of growth ability than the upper cuttings. Chaya plants used basal stem cuttings exhibited slower shoot grow but produced higher number of leaves, greater leaf area, canopy area, and biomass. The use of cow manure in a mixture of growing medium gave the best results on growth of chaya plants.